Emotion, Cognition, and Comprehension: A Psycholinguistic View in EFL Classrooms - Ariqqah Raihana; Elvida Futri Mahara; ⁠Irpi Octia Pebrianti; Yani Lubis (Lembaga Pengembangan Kinerja Dosen, 2024)
This study investigates the interconnected roles of emotion and cognition in shaping comprehension processes within EFL classrooms from a psycholinguistic perspective. Using a qualitative design involving classroom observations, semi-structured interviews, and document analysis, the research reveals that learners’ emotional states significantly influence their attentional control, working memory function, and overall ability to construct meaning. Positive emotions such as confidence and curiosity enhance cognitive efficiency, while negative emotionsm particularly anxiety disrupt processing and lead to superficial comprehension. The findings also highlight the importance of classroom environment, showing that supportive teacher interactions and collaborative peer engagement foster emotional comfort and facilitate deeper comprehension. In contrast, evaluative or high-pressure tasks trigger emotional tension that restricts cognitive readiness. Additionally, learners’ emotion regulation strategies play a critical role in sustaining engagement during challenging tasks. Overall, the study underscores that comprehension in EFL settings is a dynamic interaction between affective states, cognitive mechanisms, and classroom conditions. These insights call for pedagogical approaches that integrate emotional awareness to enhance learners’ cognitive performance and meaning-making abilities.